2016
DOI: 10.1186/s12917-016-0692-x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory response to the administration of mesenchymal stem cells in an equine experimental model: effect of autologous, and single and repeat doses of pooled allogeneic cells in healthy joints

Abstract: BackgroundMesenchymal stem cells (MSCs) transplantation has become a promising therapeutic choice for musculoskeletal injuries. Joint-related disorders are highly prevalent in horses. Therefore, these animals are considered as suitable models for testing MSC-based therapies for these diseases. The aim of this study was to investigate the clinical and inflammatory responses to intra-articular single and repeat dose administration of autologous or of pooled allogeneic MSCs in healthy equine healthy joints. Six h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
69
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 38 publications
4
69
1
1
Order By: Relevance
“…Our study did not identify any significant differences in the clinical, cytological or biomarker response of the metacarpophalangeal joint to intra‐articular injection of allogeneic vs. autologous BMDMSCs. Previous studies which administered treatments (allogeneic vs. autologous MSCs) into different joints or different cohorts of horses are in agreement with these results . In addition to cell counts and differential cytology results which have been previously reported, our study investigates a synovial inflammatory mediator (PGE 2 ) and an acute phase protein (CRP).…”
Section: Discussionsupporting
confidence: 87%
“…Our study did not identify any significant differences in the clinical, cytological or biomarker response of the metacarpophalangeal joint to intra‐articular injection of allogeneic vs. autologous BMDMSCs. Previous studies which administered treatments (allogeneic vs. autologous MSCs) into different joints or different cohorts of horses are in agreement with these results . In addition to cell counts and differential cytology results which have been previously reported, our study investigates a synovial inflammatory mediator (PGE 2 ) and an acute phase protein (CRP).…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, repeat injections of allogenic cells showed a lower degree of synovitis than the initial injection in all six horses. The characterisation of cells in this study showed that there was moderate expression of MHC I and low expression of MHC II [12]. This is in contrast with the allogenic cells from our donor which were determined to be negative for MHC II from passages 2 through 5.…”
Section: Discussioncontrasting
confidence: 73%
“…Previous studies have shown conflicting results regarding the intra‐synovial use of allogenic MSCs. Compared with control joints injected with lactated ringer's solution, 100% of joints injected with either autologous or pooled allogenic BM‐MSCs showed evidence of synovitis with mild increased total‐nuclear cell counts (TNCCs) and total protein values . The authors reported that horses in this study did not receive any systemic anti‐inflammatories.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Initial studies evaluating the efficacy of equine mesenchymal stem cells (MSCs) from mature horses for the treatment of musculoskeletal injuries used autologous cells [1][2][3][4][5][6][7], but more recently, numerous studies have been performed to evaluate the safety of allogeneic, mature equine MSCs in the hope of replacing autologous cells with allogeneic cells [8][9][10][11][12][13][14][15][16][17]. Allogeneic MSCs would allow for the immediate treatment of acute injuries with cells of known quality and sufficient quantity and eliminate the need for either bone marrow aspirate or adipose biopsy from the patient.…”
Section: Introductionmentioning
confidence: 99%